Do mergers improve operational performance: A study of the US Domestic Airline Industry - Wong, Alexander/A (2016)
This paper assesses the impact of mergers on four key operational performance metrics in the US domestic airline industry using a dataset from 2000−2015. We identify four mergers that have taken place in the last decade and study the effect of these mergers on our performance metrics. We compare the performance of our selected airlines before and after each merger, finding that performance post-merger appears to improve relative to pre-merger. We then carry out Fixed Effects Regression on our dataset to ascertain if there are any performance related benefits for airlines involved in mergers. Following this, after attempting to correct for the problem of endogeneity of the merger status of a firm we carry out Two Stage Least Squares Regression. Our results indicate that mergers can benefit the airlines in terms of improved performance though many of our results are not significant. We conclude that mergers in the Airline Industry can result in improvement in the key performance metrics we identify.